Social perception and environmental behavior of communities close to a tropical urban river in Costa Rica (UNED Research Journal, 2017)
Urban green areas are important to keep balance in the cities, but few studies consider people`s perception of these areas. We evaluated and compared the environmental perception of two urban communities in San José, Costa Rica. The analyzed communities are separated by the Ocloro River; one has a low socioeconomic status and the other a medium-high level. We conducted surveys in 40 homes located less than 150 m from the river, and local government employees in charge of natural resources management. We performed a qualitative analysis on pollution and alteration of the river and its protected zone. We assessed the state of the river's protected area and the green area per inhabitant in satellite images. We also quantified pluvial and sewage drains. Although the environmental perception is similar, behavior varies: the “low” community pours more drains into the river and has invaded 38% of the protected area; 75% of the protected area borders constructions and this facilitates invasion. This community has 19 m2 per inhabitant (108 m2 in the other); both meet United Nations Organization’s standards. Nevertheless, some green areas are off-limits to the public. There was no significant difference between communities’ in environmental perception: both identified vegetation and river as the main resource and advantage; pollution and odors as the main disadvantages; and environmental education, channel maintenance and reforestation as possible solutions. Local authorities agreed to identify wastewater and protected area invasion as major problems. We recommend participatory environmental education, especially for the low socioeconomic community.
Keywords: environmental education; protected area boundary; invasion of protected areas; infrastructure coverage; urban ecology; urban ecosystem